Uji Distribusi Binomial Pada Data Lama Masa Studi Mahasiswa - Jeni Marianti Loban; Yepsi Peringsi; Melki Imamastri Puling Tang (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2023)
The length of study time for students at a higher education institution varies quite a lot. Many factors cause students to finish college on time or not on time. The length of study period is one indicator of the success of a tertiary institution. The faster students complete their education, the better the quality of service from an educational institution. This study aims to test the binomial distribution on data on length of study of students of the Tribuana University Mathematics Study Program (Untrib) Kalabahi. The binomial distribution is a distribution of discrete random variables with n trials and two outcomes. The data was obtained from the mathematics study program (prodi) document, in the form of the length of study period of 105 graduate students in 2017-2021. Then a binomial distribution test was carried out with successful data categories, namely students who completed college ≤ 8 semesters and the failed category, namely students who completed college > 8 semesters. The results of the study show that the average success rate for mathematics students is not equal to 50% of the total students in each batch